2017
DOI: 10.3892/ol.2017.5878
|View full text |Cite
|
Sign up to set email alerts
|

Increased MIR31HG lncRNA expression increases gefitinib resistance in non-small cell lung cancer cell lines through the EGFR/PI3K/AKT signaling pathway

Abstract: The aim of the present study was to gain insight into the molecular mechanism of gefitinib resistance in non-small cell lung cancer (NSCLC), and demonstrate whether long noncoding RNA (lncRNA) expression signatures differ between gefitinib-sensitive PC9 and gefitinib-resistant PC9 (PC9-R) cell lines. PC9 and PC9-R cells were treated with gefitinib and, after 48 h, proliferation and apoptosis were analyzed using a Cell Counting Kit-8 (CCK-8) assay and flow cytometry. Microarray expression profiling of lncRNAs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 39 publications
1
53
0
Order By: Relevance
“…For example, in clear cell renal cell carcinoma, lncRNA MRCCAT1 can induce tumor metastasis through inhibiting NPR3 and activating p38‐MAPK signaling (Li et al, ). Upregulation of lncRNA MIR31HG expression promotes gefitinib resistance in NSCLC cell lines by activating EGFR/PI3K/AKT signaling pathway (Wang, Jiang, et al, ). In lung cancer, microRNA‐449a can inhibit cell growth by regulating lncRNA NEAT1 (You et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in clear cell renal cell carcinoma, lncRNA MRCCAT1 can induce tumor metastasis through inhibiting NPR3 and activating p38‐MAPK signaling (Li et al, ). Upregulation of lncRNA MIR31HG expression promotes gefitinib resistance in NSCLC cell lines by activating EGFR/PI3K/AKT signaling pathway (Wang, Jiang, et al, ). In lung cancer, microRNA‐449a can inhibit cell growth by regulating lncRNA NEAT1 (You et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al . revealed that overexpression of MIR31HG lncRNA contributes to gefitinib resistance in NSCLC cell lines, affecting cell proliferation, apoptosis, and the cell cycle by activating the EGFR/PI3K/AKT pathway …”
Section: Lncrnas and Egfr‐tyrosine Kinase Inhibitor (Tki) Resistancementioning
confidence: 99%
“…71 Wang et al revealed that overexpression of MIR31HG lncRNA contributes to gefitinib resistance in NSCLC cell lines, affecting cell proliferation, apoptosis, and the cell cycle by activating the EGFR/PI3K/AKT pathway. 72 LncRNA UCA1 was first identified in bladder cancer cells and is involved in the invasion and progression of bladder cancer. 73 In lung cancer, overexpression of UCA1 induces non-T790M acquired resistance to EGFR-TKIs by activating the AKT/mTOR pathway.…”
Section: Lncrnas Promote Egfr-tki Resistance By Regulating the Cell Smentioning
confidence: 99%
“…MIR31HG was a LncRNA, identified as >2166 nucleotides in length . Recent studies showed that increased MIR31HG expression increased gefitinib resistance in NSCLC lines through the EGFR/PI3K/AKT signalling pathway . Zheng et al also discovered MIR31HG could promote the invasion of NSCLC by activating the Wnt/β‐catenin signalling pathway …”
Section: Main Molecular Mechanism Of Lncrna To Regulate the Metastasimentioning
confidence: 99%